Management of chest tube after thoracoscopic lung resection in children with congenital lung malformation: a multicenter retrospective study - Kaisheng Cheng; Miao Yuan; Gang Yang; Taozhen He; Dengke Luo; Chenyu Liu; Zongyu Wang; Jiayin Yang; Fei Li; Guangxian Yang; Yonggang Li; Chang Xu (Scientific Reports)
Abstract This study aimed to investigate the safety and effect of omitting chest tubes after thoracoscopic lobectomy in children with congenital lung malformation. A multicenter retrospective study was performed with 632 thoracoscopic lobectomy CLM patients in four hospitals between 2014.1 and 2023.1, which were divided into non-chest tube (NCT)group and chest tube (CT)group. Baseline data, operation and follow-up outcomes were compared. In total, 312 patients were included in the NCT group, and 320 in the CT group. There were no statistically significant differences in baseline data between the two groups. The FLACC scale score in the NCT group was less than the CT group (2.7 ± 0.43 vs. 5.8 ± 0.26 p = 0.027). The median length of postoperative hospital stay in the CT group was significantly longer than the NCT group (5 d vs.3 d, p = 0.045). Eight (2.5%) patients developed chest tube related infections in the CT group(p = 0.004). Six patients developed atelectasis in the NCT group, which was significantly less than the 18 patients in the CT group(p = 0.014). No chest tube placement in selected CLM pediatric patients may be safe and avoid chest tube-related complications, which may also contribute to a rapid recovery.